2017
DOI: 10.1080/10610278.2017.1401074
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and inclusion properties of G-series chemical warfare agents and their simulants: a DFT study

Abstract: A computational protocol to predict the infrared spectra of chemical warfare agents (CWAs) tabun (GA), sarin (GB), soman (GD) and cyclosarin (GF) has been developed. Sarin was used to benchmark the method through gas phase simulations. DFT calculations using the EDF2 functional and diffuse 6-311++G** basis set was found to give the closest match to experimental infrared spectra. Using the same functional the 6-31G (2df, 2p) basis set was found to be superior when hydrated sarin was modelled. GA, GB, GD and GF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…In the case of the anions, a fluoride or chloride was introduced, optimization repeated and refined by semiempirical methods (PM3). These coordinates were used as the input for geometry optimization by DFT using the EDF2/6‐31G* theoretical model we have previously found accurate for systems with significant hydrogen bonding …”
Section: Methodsmentioning
confidence: 99%
“…In the case of the anions, a fluoride or chloride was introduced, optimization repeated and refined by semiempirical methods (PM3). These coordinates were used as the input for geometry optimization by DFT using the EDF2/6‐31G* theoretical model we have previously found accurate for systems with significant hydrogen bonding …”
Section: Methodsmentioning
confidence: 99%
“…Here, we identify three trends, one for the phosphoryl species and two for the sulfonyl species. The two trends identified for the sulfonyl species correspond to the two different classes of sulfonate molecules present within the library of simulants studied, those substituted with a toluene group (16)(17)(18)(19)(20) and those substituted with a methyl group (21)(22)(23)(24)(25)(26). As the limitation of the experimental association constant determination methodology is ≈10 M −1 , we suggest that any values incorporating ≤10 M −1 may be considered inappropriate when included into a model such as this and should be treated with caution.…”
Section: Single Parameter Predictive Modelsmentioning
confidence: 89%
“…It is therefore vital to consider the appropriate properties of any simulant chosen to aid in the development of novel OP CWA detection, decontamination, or remediation methodologies. [21][22][23][24] Recently, work undertaken by Snurr and Mendonca, has shown that density functional theory (DFT) can be used to study the mechanism of OP hydrolysis, which has resulted in the development of a quantitative structure activity relationship (QSAR) model that enables the identification of appropriate OP CWA simulants for decontamination purposes. 25 However, when considering supramolecular technologies, the moiety target is often selective coordination of the polar PvO functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of computational methods allowed for deconvolution of association constants to calculate diastereoisomer-specific complex affinities of the four diastereoisomers of GD [P(+)C(+), P(+)C(−), P(−)C(−), P(−)C(+)] [ 23 ]. A further theoretical study has considered the formation of inclusion complexes of the CWA GB and a range of simulants by α-cyclodextrin, alongside spectroscopic calculations for the V-series agents VX and VG and the G-series agents GA, GB, GD and GF [ 24 ].…”
Section: Introductionmentioning
confidence: 99%